Hubungan antara ideologi nasional dan kinerja timnas nasional indonesia dalam kejuaraan internasional - Ramadhani, Nandhika Bagus (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the relationship between Indonesia’s national ideology, as reflected in Pancasila, and the performance of the Indonesian National Football Team in international football tournaments. The main focus of this research is to understand how values contained in Pancasila, such as unity, mutual cooperation, and national spirit, can influence the fighting spirit, team cohesion, and individual performance at the international level. A qualitative descriptive approach is used, with data collection techniques including literature review, in-depth interviews, observations, and documentation. The findings of the study indicate that Indonesia’s national ideology plays a significant role in shaping the players’ character, strengthening national spirit, and improving the Indonesian National Team’s performance in international competitions. The spirit of unity and cooperation reflected in Pancasila serves as a driving force supporting team cohesion and a champion mentality. This research is expected to contribute to the development of a national ideology-based training strategy for the Indonesian National Football Team and reinforce the integration of national values in the world of sports.